Fruit grading machine. - Shamsuddin, Rosnah (2009)

(untitled)
The present innovation relates to a conveying device which grades the fruit according to their weight and the grading process is in accordance specifications and standard. The invention includes a conveyor belt (1) which is motorized and consist a series of mechanical weights (100). These weighing units (100) each have a mechanical sensor (4) for weight measurement as the fruis are being conveyed on the conveyor belt (1). As the fruit reaches a weighing unit (100), the fruits on the weighing plate (3) would be weighied using a mechanical weigher (2) and if it falls under the specified weight range, the sensors indicator (5) would be triggered. This will activate the pneumatic cylinder (7) to eject the fruit into the storage section. If the fruit does not fall within the specified weight range, the fruit will be conveyed to the next weighing unit (100) and similar process is repeated.